2011
DOI: 10.1089/ars.2010.3486
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection by Endoplasmic Reticulum Stress–Induced Autophagy

Abstract: This study tested the hypothesis that the induction of autophagy by producing therapeutic amounts of endoplasmic reticulum (ER) stress in the heart before an ischemic insult would ameliorate/reduce subsequent lethal myocardial ischemic/reperfusion (I/R) injury (similar to ischemic preconditioning). A dose-response study with both tunicamycin and thapsigargin was performed to determine the optimal dose (0.3 mg/kg) for inducing autophagy for cardioprotection. The Sprague-Dawley rats weighing between 250 and 300 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
76
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(91 citation statements)
references
References 25 publications
12
76
1
2
Order By: Relevance
“…Several lines of evidence demonstrated that ER stress contributes to autophagy activation [25][26][27][28] . An essential step in ER stress-induced autophagosome formation is the phosphorylation of PERK/eIF2α.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several lines of evidence demonstrated that ER stress contributes to autophagy activation [25][26][27][28] . An essential step in ER stress-induced autophagosome formation is the phosphorylation of PERK/eIF2α.…”
Section: Discussionmentioning
confidence: 99%
“…If ER stress is mild, cells will express an adaptive response through autophagy and will survive during subsequent lethal ischemia. If ER stress is overwhelming, however, the cells will die through ER stress-related apoptosis [26] . Caspase-12, a murine protein that is associated with the ER membrane, is involved in ER stress-dependent apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, autophagy produced with lower doses of ER stress inducers results in protection against ischemic/reperfusion injury in heart. 47 Nonetheless, under chronic ER stress, an excessive and uncontrolled autophagic activation can lead to the depletion of essential molecules and organelles, which triggers autophagic cell death. This form of cell death has recently been shown to play an important role in the development of ER stress-associated cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…ER stress enhances autophagy by negatively regulating the AKT/TSC/mTOR pathway [27] . ER stress inducers such as brefeldin A, thapsigargin and tunicamycin increase the formation of autophagic vesicles with the expression of Beclin and LC-3 (microtubule-associated protein1 light chain 3) II, two autophagic markers [28,29] . However, conflicting data have also been reported.…”
Section: Starvation Inducersmentioning
confidence: 99%